THE ROLE OF ECONOMIC LAW AND HEALTH LAW IN DIVERSION AND RESTORATIVE JUSTICE FOR PETTY THEFT OFFENDERS: A LITERATURE REVIEW - Gunawan Widjaja (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2025)
This study aims to examine the role of economic law and health law in the implementation of diversion and restorative justice for petty theft offenders through a literature review approach. The results of the study show that the integration of economic law in the diversion process provides a concrete solution in the form of a compensation scheme that considers the economic capacity of the offender as well as an economic empowerment programme to prevent recidivism. Meanwhile, health law plays an important role in supporting the physical and psychosocial rehabilitation of offenders, especially those with mental health problems, so that recovery does not only focus on legal aspects, but also on improving the overall quality of life of offenders. The integration of these two areas of law in diversion and restorative justice mechanisms can create a more humane, fair and sustainable case resolution system, while strengthening the protection of human rights and supporting the social reintegration of offenders into society.